Pendampingan dan Implementasi Teknologi Panel Surya Berpendingin Water spray Untuk Kemandirian Energi dalam Mendukung “Program Kampung Iklim” Di Kelurahan Loktabat Utara Kota Banjarbaru - Irawansyah, Herry; Amrullah, Apip; Ansyah, Pathur Razi; Pagis, Arifah; Lukmana, Wahyu (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
This research aims to study the mentorship and implementation of water-spray-cooled solar panel technology as an initiative to support energy independence within the Kampung Iklim Program in Loktabat Utara, Banjarbaru City. Using survey methods, system design, equipment construction, and community involvement, the program identifies local energy needs and designs an optimized solar panel system incorporating water spray cooling technology to enhance efficiency. The implementation results demonstrate a significant increase in solar panel efficiency, with reduced operational temperatures and increased energy output. This technology also positively impacts greenhouse gas emission reduction and improves the quality of life by providing more affordable energy access and creating job opportunities. This research confirms the potential of water-spray-cooled solar panels in achieving energy independence and supporting climate change mitigation efforts at the local level.